2019
DOI: 10.33710/sduijes.596569
|View full text |Cite
|
Sign up to set email alerts
|

Parents' Educational Expectations: Does It Matter for Academic Success?

Abstract: In this journal, research articles which reflect the survey with the results and translations that can be considered as a high scientific quality, scientific observation and review articles are published. Teachers, students and scientists who conduct research to the field (e.g. articles on pure sciences or social sciences, mathematics and technology) and in relevant sections of field education (e.g. articles on science education, social science education, mathematics education and technology education) in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 34 publications
0
4
0
1
Order By: Relevance
“…Previous studies have demonstrated that parents' academic expectations influence students' academic achievements, especially for primary and secondary school students (Nihal Lindberg et al, 2019 ). However, for college students, most studies emphasized the psychological pressure and anxiety caused by parents' academic expectations while ignoring the positive role (Cooper and Cefai, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that parents' academic expectations influence students' academic achievements, especially for primary and secondary school students (Nihal Lindberg et al, 2019 ). However, for college students, most studies emphasized the psychological pressure and anxiety caused by parents' academic expectations while ignoring the positive role (Cooper and Cefai, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Analyses performed on the data obtained from Turkish students' schools and family characteristics on exams such as the PISA and TIMMS (Taş et al, 2016;Yıldırım et al, 2013) revealed that the most important variables affecting achievement are the family-related variables. Although there are two studies on parental cognition in the Turkish literature (Lindberg et al, 2019;Kaya & Bacanlı, 2016), it was not encountered with a study examining its direct effect on academic achievement. Accordingly, the present study aims to examine the effects of PI and parental expectations on the academic achievement of students aged between 10 and 13.…”
Section: Significance and Purpose Of The Researchmentioning
confidence: 99%
“…They found that parents' acknowledgment of the importance of their self-efficacy levels for supporting the education of their children and their own positive school experiences also increased their participation in the education of their children. Lindberg et al (2019) designed a qualitative study based on interviews. The study focused on the expectations of parents regarding the educational future of their children.…”
Section: Purpose and Significance Of The Studymentioning
confidence: 99%
“…Bununla birlikte, özellikle ana baba katılımına yönelik çalışmalarda gerek ana babaların gerekse öğretmen ve yöneticilerin katılımın önemi ve gerekliliğine inanıyor olmalarına rağmen, eğitimde ana baba katılımının sınırlı ve hatta yokluğunu ortaya koyan bulgular, bunun nedeni ile ilgili daha ayrıntılı incelemeler yapılmasını gerektirmektedir. Ancak alanyazında katılımı engelleyen ana babaya, okula, çocuğun kendisine özgü kimi özelliklere (eğitim düzeyi, sosyoekonomik düzey, çalışma durumu, işbirliğine açık olmama, katılımla ilgili olumsuz tutum gibi) değinilmekle birlikte (Basaran & Koc, 2001;Ceylan & Akar, 2011;Erdogan & Demirkasımoglu, 2010;Keçeli-Kaysılı, 2002;Lindberg, 2013;Sabancı, 2009;Şad, 2012), üç çalışma dışında (Kaya & Bacanlı, 2015;Lindberg, Yıldırım, Elvan, Öztürk &Recepoğlu, 2019;Tekin, 2016) ana babaların çocuklarının eğitimindeki rolleri ile ilgili inanç ve değerleri ve özelde de başarıya dönük kişisel ve kültürel temelli yüklemelerini belirlemeye yönelik herhangi bir çalışmaya rastlanmamıştır. Kaya ve Bacanlı (2015)'nın çalışmasında, ana babaların çocuklarının eğitimine katılımları ile ilgili rol ve yeterlilik algıları üzerinde durulmuştur.…”
Section: Araştırmanın Amacı Ve öNemiunclassified